Llefa Lame: [Re]imaging Soshanguve Landfill - Molubi, Lefentse (School of Architecture, Planning and Geomatics, 2023)
Twenty-seven (27) years of democracy in South Africa, communities in townships formed by the apartheid government, live in dire conditions brought by the legacy of apartheid. The lack of economic opportunities and resources make South African citizens creative and innovative, communities from Pretoria north townships gather daily at municipal landfills to collect, sort valuable and recyclable waste in exchange for cash. This study focuses on informal waste re-claimers working conditions at Soshanguve landfill and Soshanguve township communities residing in the vicinity of an active landfill that is situated within an environment that is rich in history and heritage. The aim of this study is to investigate the daily activities of the informal waste re-claimers; and hopes to inform innovative and functional ways to create a tolerable working environment during the operational phases of the landfill with the intention of transforming it to a sustainable public open space upon decommission. The study approach considers a pragmatic research using both qualitative and quantitative study methods to collect data through In-depth interviews, statistical observations and theoretical investigation.